Adult tribal malnutrition in India: an anthropometric and socio-demographic review - Das, Subal; Bose, Kaushik (Anthropological Review, 2015)
The nutritional status and socio-demographic profile of tribal people is an important issue in India due to their marginalization from main stream population with respect to varied facilities. However, data on their nutritional status and socio-demographic profile are limited. This review aims to give an overview of the prevalence of chronic energy deficiency (CED) using Body mass index (BMI) and various demographic profile of Indian tribes based on studies published hitherto. In total 76 studies were reviewed for mean BMI based on the World Health Organization (WHO) classification of the public health problem of low BMI, based on adult populations worldwide. The overall sex specific prevalence of CED showed that both the tribal females (52.0%) and males (49.3%) were passing through the critical situation with respect to nutritional status with females being more underprivileged. In conclusion, although there is a gradual increase in knowledge about the nutritional and socio-demographic status of tribes since last decades; there is still paucity of data and information on more than approximately 600 tribes regarding their bio-social profile. However previous studies clearly indicate the need to enhance the health and nutrition status of the tribes by providing job opportunity and food security. Since the prevalence of CED was higher (critical to serious situation) in tribal populations, concerted efforts should also be made to improve the health status and nutrition uptake among them.